УЛААГЧИНЫ ХАР НУУРЫН МОРФОЛОГИЙН ГАРАЛ ҮҮСЭЛ - Э., Алтанболд; Х., Уламбадрах; Б., Даариймаа; Ц., Баатарчулуун; Б., Даш (Geological Issues, 2022)
Information about the depression origin of some lakes is out in previous studies on the genetics and morphology of lakes in Mongolia. One example of these is the genetics of Ulaagchinii Kharnuur. The site research was done by using the morpho-structural method and integrated the results in topographic and satellite images implementing the softwares such as remote sensing and etc. Ulaagchinii Kharnuur is a freshwater lake supplied with the deep water due to tectonic faults. In other words, thaw depression at the middle of Ulaagchinii Kharnuur basin is may be related to the tectonic fault from northwest to the southeast. The Ulaagchinii Kharnuur is very much defined as the lakes which are large, deep and with steep bed are inequalities in the tectonic fault lakes, and the lake’s depression is narrow and heavily shaped. It proposes the tectonic origin for Ulaagchinii Kharnuur which origin was recorded as having an Aeolus.